THE EFFECT OF ENTREPRENEURSHIP EDUCATION AND ENTREPRENEURSHIP CHARACTERISTICS IN INCREASING INTEREST IN ENTREPRENEURSHIP IN FIRST MIDDLE SCHOOL STUDENTS - Aprilda Yanti (Enrichment : Journal of Management, 2021)
This research was conducted to determine the effect of (1) entrepreneurship education on students' interest in entrepreneurship (2) entrepreneurial characteristics on students' entrepreneurial interests, (3) entrepreneurship education and entrepreneurial characteristics on students' entrepreneurial interests. This research uses descriptive quantitative method. The population is all grade IX SMP EMPLOYEES Tanjung Morawa totaling 150 students. The sample is 30 students and uses proportional random sampling as a sampling technique. Collecting data using a questionnaire. The results of this study (1) there is a significant influence between Entrepreneurship Education on Entrepreneurial Interest in students (2) there is a significant effect of Entrepreneurial Characteristics on Entrepreneurial Interest in students (3) Entrepreneurship Education variables and Entrepreneurial Characteristics, together have a positive and significant to students' interest in entrepreneurship.